The follicular microenvironment in low (++) and high (I+B+) ovulation rate ewes. Issue 5 (May 2020) - Clark, Zaramasina L; Heath, Derek A; O'Connell, Anne R; Juengel, Jennifer L; McNatty, Kenneth P; Pitman, Janet L
Abstract : Ewes with single copy mutations in GDF9, BMP15 or BMPR1B have smaller preovulatory follicles containing fewer granulosa cells (GC), while developmental competency of the oocyte appears to be maintained. We hypothesised that similarities and/or differences in follicular maturation events between WT (++) ewes and mutant ewes with single copy mutations in BMP15 and BMPR1B (I+B+) are key to the attainment of oocyte developmental competency and for increasing ovulation rate (OR) without compromising oocyte quality. Developmental competency of oocytes from I+B+ animals was confirmed following embryo transfer to recipient ewes. The microenvironment of both growing and presumptive preovulatory (PPOV) follicles from ++ and I+B+ ewes was investigated. When grouped according to gonadotropin-responsiveness, PPOV follicles from I+B+ ewes had smaller mean diameters with fewer GC than equivalent follicles in ++ ewes (OR = 4.4 ± 0.7 and 1.7 ± 0.2, respectively; P < 0.001). Functional differences between these genotypes included differential gonadotropin-responsiveness of GC, follicular fluid composition and expression levels of cumulus cell-derived VCAN, PGR, EREG and BMPR2 genes. A unique microenvironment was characterised in I+B+ follicles as they underwent maturation. Our evidence suggests that GC were less metabolically active, resulting in increased follicular fluid concentrations of amino acids and metabolic substrates, potentially protecting the oocyte from ROS. Normal expression levels of key genes linked to oocyte quality and embryo survival in I+B+ follicles support the successful lambing percentage of transferred I+B+ oocytes. In conclusion, these I+B+ oocytes develop normally, despite radical changes in follicular size and GC number induced by these combined heterozygous mutations.